Improving The Creation Of Software Based On The Organization Of Independent Learning Of Students (Journal of Pedagogical Inventions and Practices, 2025)
This article examines the issue of improving educational software development based on the organization of students’ independent learning. Software tools developed using modern pedagogical and technological approaches enhance interactivity, personalization, and learning efficiency. The study outlines the stages of designing such software, methods for identifying user needs, and implementing modular architecture. The effectiveness of the developed tool is assessed based on an experimental study conducted in two student groups.